Neck circumference in children and adolescents –an emerging tool for screening central obesity - Malini, M; Kalpana, S; Lakshmi, S (Indian Journal of Child Health, 2025)
Objectives: The aim of the study was to validate the utility of neck circumference (NC) as an anthropometric measure of the central obesity and its correlation with body mass index (BMI) and waist circumference (WC). The aim of the study was to determine age and gender specific NC cutoffs for screening central obesity. Materials and Methods: This descriptive study was conducted in 1139 children and adolescents aged 6–17 years. NC, WC, and BMI were measured. To define overweight and obesity in children, the 23rd and 27th adult equivalent lines for BMI as presented in the revised Indian Academy of Pediatrics growth charts were used. Results: Overweight and obese children had significantly higher NC than those with normal BMI (p<0.001). NC showed a positive correlation with both WC and BMI (p<0.001). In children aged <12 years, NC cutoff for screening obesity was 26.5 cm in both boys (sensitivity 83.3% and specificity 71.7%) and girls (81.4% and 70.5%). The area under the curve for NC was greater than that of WC in both boys (0.86 vs. 0.76) and girls (0.82 vs. 0.66). In children aged 12–17 years, NC cutoff values were 34 cm in boys (sensitivity 83.33% and specificity 75.60%) and 31 cm in girls (94.34% and 83.29%). The area under curve for WC was greater than that of NC in boys (0.94 vs. 0.88) and almost similar in girls (0.96 vs. 0.95). Conclusions: NC can accurately identify children with a high BMI. It is a better anthropometric measure than WC in identifying prepubertal children with central obesity. In children aged 12–17 years, it can be considered a good alternative for screening central obesity.